Nonthermal atmospheric pressure plasma (NTAPP) effectively eliminates skin tumors in a mouse model of UV-induced carcinogenesis with a short-term treatment regimen - Szabolcs Bozsányi; Ruby Acquah; Rhea Carmel Glen Rodrigues; Erin C. Tracy; Sean P. Murphy; Gregory Fridman; Wendy J. Huss; Peter C. Friedman; Gyorgy Paragh (Journal of Photochemistry and Photobiology)
Introduction: Nonthermal atmospheric pressure plasma (NTAPP) therapy has emerged as a promising modality in dermatology for wound healing, tissue regeneration, and anti-tumor applications. This study evaluated the feasibility and effectiveness of a simple, one-week NTAPP treatment protocol in the SKH1 hairless mouse model of chronic ultraviolet (UV) radiation-induced carcinogenesis. Materials and methods: SKH1 mice were exposed to solar-simulated UV light 5 times a week for 10 weeks, which produced multiple skin tumors on each mouse. At week 25 NTAPP treatment was administered to a subgroup of mice at a setting of 20 kV with a 20 ns pulse width and 200 Hz frequency three times within a single week. A total of 31 NTAPP-treated and 34 internal control tumors (i.e., nearby tumors on the same mouse) in UV-exposed, NTAPP-treated mice were evaluated for tumor size at 0 and 28 days after the beginning of the treatment by using ImageJ on standardized photographs. A subset of the tumors was also assessed with a 33 MHz high-frequency ultrasound (HFUS) to measure vertical tumor thickness. In similarly housed control mice, sizes of 64 tumors were evaluated as external controls. Results: NTAPP induced a significant reduction in the mean tumor area from 5.65 ± 6.51 mm² before treatment to 1.74 ± 3.99 mm² 28 days post-treatment (paired t-test, p = 0.0016). Internal control tumors, in contrast, showed an increase in area from 3.24 ± 2.54 mm² before treatment to 4.57 ± 3.58 mm² 28 days post-treatment (paired t-test, p = 0.0296). Of the 31 treated tumors, 23 completely disappeared; in contrast, only six non-treated internal control tumors disappeared (p = 0.0139, two-sided chi-square test). Simultaneously, optically guided HFUS revealed a significant decrease in tumor thickness in treated areas (paired t-test, p = 0.0006), with no significant changes observed in the internal control tumors (paired t-test, p = 0.5555). External control tumors showed an increase in size, which was not statistically significant. Discussion: The results demonstrated that a one-week NTAPP protocol could effectively eliminate 74 % of mouse tumors induced by UV radiation. These findings warrant further investigations of short, clinically feasible NTAPP treatment protocols for early skin cancer treatment.